Clinical Validation of the Glenoid Track Concept in Anterior Glenohumeral Instability. (16th November 2016) - Shaha, James S.; Cook, Jay B.; Rowles, Douglas J.; Bottoni, Craig R.; Shaha, Steven H.; Tokish, John M.
Abstract : Background: Glenoid and humeral bone loss are well-described risk factors for failure of arthroscopic shoulder stabilization. Recently, consideration of the interactions of these types of bone loss (bipolar bone loss) has been used to determine if a lesion is "on-track" or "off-track." The purpose of this study was to study the relationship of the glenoid track to the outcomes of arthroscopic Bankart reconstructions. Methods: Over a 2-year period, 57 shoulders that were treated with an isolated, primary arthroscopic Bankart reconstruction performed at a single facility were included in this study. The mean patient age was 25.5 years (range, 20 to 42 years) at the time of the surgical procedure, and the mean follow-up was 48.3 months (range, 23 to 58 months). Preoperative magnetic resonance imaging was used to determine glenoid bone loss and Hill-Sachs lesion size and location and to measure the glenoid track to classify the shoulders as on-track or off-track. Outcomes were assessed according to shoulder stability on examination and subjective outcome. Results: There were 10 recurrences (18%). Of the 49 on-track patients, 4 (8%) had treatment that failed compared with 6 (75%) of 8 off-track patients (p = 0.0001). Six (60%) of 10 patients with recurrence of instability were off-track compared with 2 (4%) of 47 patients in the stable group (p = 0.0001). The positive predictive value of an off-track measurement was 75% compared with 44% for the predictive value of glenoid bone loss of >20%. Conclusions: The application of the glenoid track concept to our cohort was superior to using glenoid bone loss alone with regard to predicting postoperative stability. This method of assessment is encouraged as a routine part of the preoperative evaluation of all patients under consideration for arthroscopic anterior stabilization. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.